New functional chiral P-based ligands and application in ruthenium-catalyzed enantioselective transfer hydrogenation of ketones. Issue 12 (15th December 2017) - Meriç, Nermin; Kayan, Cezmi; Gürbüz, Nevin; Karakaplan, Mehmet; Binbay, Nil Ertekin; Aydemir, Murat
Graphical abstract: Abstract: Metal-catalyzed asymmetric transfer hydrogenation is a powerful and practical method for the reduction of ketones to produce the corresponding secondary alcohols, which are valuable building blocks in the pharmaceutical, perfume, and agrochemical industries. Hence, a series of novel chiral β -amino alcohols were synthesized by chiral amines with regioselective ring opening of ( S )-propylene oxide or reaction with ( S )-(+)-2-hydroxypropyl p -toluenesulfonate by a straightforward method. The chiral ruthenium catalytic systems generated from [Ru(arene)(μ-Cl)Cl]2 complexes and chiral phosphinite ligands based on amino alcohol derivatives were employed in asymmetric transfer hydrogenation of ketones to give the corresponding optically active alcohols; (2 S )-1-{[(2 S )-2-[(diphenylphosphanyl)oxy]propyl][(1 R )-1-phenylethyl]amino}propan-2-yldiphenylphosphinitobis[dichol-oro(η 6 -benzene)ruthenium(II)] acts an excellent catalyst in the reduction of α -naphthyl methyl ketone, giving the corresponding alcohol with up to 99% ee. The substituents on the backbone of the ligands were found to have a remarkable effect on both the conversion and enantioselectivity of the catalysts. Furthermore, this transfer hydrogenation is characterized by low reversibility under these conditions. Abstract : ( S )-1-[ N -( R )-α-Phenylethyl]amino-2-propanole: C11 H17 NO [ α ]D 20  = +83.4 ( c 1, CH2 Cl2 ) Absolute configuration: ( S, R ) Abstract : (2 S )-1-{[(2 S )-2-Hydroxypropyl][(1 R )-phenylethyl]amino}propan-2-ol: C14 H23 NO2 [ α ]D 20  = +65.8 ( c 1, CH2 Cl2 ) Absolute configuration: ( S, S, R ) Abstract : (2 S )-1-{[(1 R )-1-Phenylethyl]amino}propan-2-yl diphenylphosphinite: C23 H26 NOP [ α ]D 20  = +28.3 ( c 1, CH2 Cl2 ) Absolute configuration: ( S, R ) Abstract : (2 S )-1-{[(2 S )-2-[(Diphenylphosphanyl)oxy]propyl][(1 R )-1-phenylethyl]amino}propan2-yl diphenylphosphinite: C38 H41 NO2 P2 [ α ]D 20  = −8.2 ( c 1, CH2 Cl2 ) Absolute configuration: ( S ) Abstract : (2 S )-1-{[(1 R )-1-Phenylethyl]amino}propan-2-yl diphenylphosphinito[dichloro (η 6 - p -cymene) ruthenium (II)]: C33 H40 NOPRuCl2 [ α ]D 20  = +23.0 ( c 1, CH2 Cl2 ) Absolute configuration: ( S, R ) Abstract : (2 S )-1-{[(1 R )-1-Phenylethyl]amino}propan-2-yl diphenylphosphinito[dichloro(η 6 -benzene) ruthenium (II)]: C29 H32 NOPRuCl2 [ α ]D 20  = +10.0 ( c 1, CH2 Cl2 ) Absolute configuration: ( S, R ) Abstract : (2 S )-1-{[(2 S )-2-[(Diphenylphosphanyl)oxy]propyl][(1 R )-1-phenylethyl]amino} propan-2-yl diphenylphosphinitobis[dichloro(η 6 - p -cymene)ruthenium(II)]2: C58 H69 NO2 P2 Ru2 Cl4 [ α ]D 20  = −42.0 ( c 1, CH2 Cl2 ) Absolute configuration: ( S, S, R ) Abstract : (2 S )-1-{[(2 S )-2-[(Diphenylphosphanyl)oxy]propyl][(1 R )-1-phenylethyl]amino}pro-pan-2-yldiphenylphosphinitobis[dichloro(η 6 -benzene)ruthenium(II)]: C50 H53 NO2 P2 Ru2 Cl4 [ α ]D 20  = −53.0 ( c 1, CH2 Cl2 ) Absolute configuration: ( S, S, R )